Decoding the role of the RNA binding activity of p53 - Moore, SL (2020)
p53 is a key tumour suppressor, mutated in over half of cancers. p53’s ability to form extensive protein interactions, along with its function as a sequence-specific transcription factor, are well documented due to their roles in canonical p53 tumour suppressor functions. Still lacking is clarity regarding p53’s ribonucleic acid (RNA) binding activity. Previously reported, predominantly acellular and in vitro results provide little in regards to the physiological relevance, biological function and underlying mechanisms of p53-RNA interactions. Here I demonstrate p53 binds polyadenylated RNA in living cells using RNA interactome capture. Further investigation of p53-RNA interactions using conventional immunoglobulin G (IgG) antibody-based approaches proves problematic. I therefore generated an inducible cell line expressing green fluorescent protein conjugated p53 (GFP-p53), enabling highly specific purification of GFP-p53. Utilising CLIP-seq, I identified a defined subset of messenger RNAs (mRNAs) bound by p53, representing a translational programme distinct from p53's transcriptional targets. Additionally, RNase coupled proteomic analysis reveals the importance of RNA in p53's protein interaction network, including the DNA damage response. This work provides evidence of a p53 post-transcriptional regulatory layer, which warrants further investigation.